PENERAPAN METODE LATIHAN PADA MATA KULIAH KALKULUS I DENGAN MENGGUNAKAN MODEL LESSON STUDY - Syutaridho Syutaridho (Jurnal Pendidikan Matematika RAFA, 2015)
Drill method aim to train to achieve fluency in mathematical calculations formal drill method also have the potential to spur the students carefully and quickly in math facts. Application of the method of exercise shows that students can perform mathematical formal settlement, and it can be said that the students still understand the concept of matter that they get at the high school level, where students exercise value >70 in each group. The conclusion of the application of training methods, namely: 1). Application of the method of exercise requires students to relate the understanding/concept they can be at the level of secondary school (high school) so that learning becomes meaningful., 2). An increase in average student training results at each meeting of 8.4 at the first meeting be 9.15 at the second lesson